Correction: Green synthesis of Pd nanoparticles supported on reduced graphene oxide, using the extract of Rosa canina fruit, and their use as recyclable and heterogeneous nanocatalysts for the degradation of dye pollutants in water. Issue 40 (20th June 2018) - Hemmati, Saba; Mehrazin, Lida; Ghorban, Hedieh; Garakani, Samira Hossein; Mobaraki, Taha Hashemi; Mohammadi, Pourya; Veisi, Hojat
Abstract : Correction for 'Green synthesis of Pd nanoparticles supported on reduced graphene oxide, using the extract of Rosa canina fruit, and their use as recyclable and heterogeneous nanocatalysts for the degradation of dye pollutants in water' by Saba Hemmati et al., RSC Adv., 2018, 8, 21020–21028.